Minimalist Sape: The Use of Digital Sound Effects For a Musical Hybrid Concept Between Dayak Sape Music and Minimalist Music - Darlene, Esther (Universitas Negeri Surabaya, 2023)
Sape Minimalist music composition is the result of a musical dialogue between Sape (Dayak) music and Minimalist music through a hybrid approach. Minimalist music itself is a backlash mainly against the chaos and complexity of serialism and aleatoric music. In minimalist music, short melodic patterns with clear tonality and constant repetition are the main focus. In this Minimalist Sape composition, the Sape instrument is usually played for specific functions such as accompanying ritual ceremonies/customs, as well as entertainment, in this composition Sape collaborates with minimalist music elements and produces a repertoire that can be classified in the